Apigenin and Luteolin Regulate Autophagy by Targeting NRH-Quinone Oxidoreductase 2 in Liver Cells - Elzbieta Janda; Concetta Martino; Concetta Riillo; Maddalena Parafati; Antonella Lascala; Vincenzo Mollace; Jean A. Boutin (MDPI AG, 2021)
Dietary flavonoids stimulate autophagy and prevent liver dysfunction, but the upstream signaling pathways triggered by these compounds are not well understood. Certain polyphenols bind directly to NRH-quinone oxidoreductase 2 (NQO2) and inhibit its activity. NQO2 is highly expressed in the liver, where it participates in quinone metabolism, but recent evidence indicates that it may also play a role in the regulation of oxidative stress and autophagy. Here, we addressed a potential role of NQO2 in autophagy induction by flavonoids. The pro-autophagic activity of seven flavonoid aglycons correlated perfectly with their ability to inhibit NQO2 activity, and flavones such as apigenin and luteolin showed the strongest activity in all assays. The silencing of NQO2 strongly reduced flavone-induced autophagic flux, although it increased basal LC3-II levels in HepG2 cells. Both flavones induced AMP kinase (AMPK) activation, while its reduction by AMPK beta (PRKAB1) silencing inhibited flavone-induced autophagy. Interestingly, the depletion of NQO2 levels by siRNA increased the basal AMPK phosphorylation but abrogated its further increase by apigenin. Thus, NQO2 contributes to the negative regulation of AMPK activity and autophagy, while its targeting by flavones releases pro-autophagic signals. These findings imply that NQO2 works as a flavone receptor mediating autophagy and may contribute to other hepatic effects of flavonoids.